2018
DOI: 10.1038/s41467-018-07385-6
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic formation of condensed carbonaceous matter in the hydrating oceanic crust

Abstract: Thermodynamic modeling has recently suggested that condensed carbonaceous matter should be the dominant product of abiotic organic synthesis during serpentinization, although it has not yet been described in natural serpentinites. Here we report evidence for three distinct types of abiotic condensed carbonaceous matter in paragenetic equilibrium with low-temperature mineralogical assemblages hosted by magma-impregnated, mantle-derived, serpentinites of the Ligurian Tethyan ophiolite. The first type coats hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…Vibrational modes characteristic for thermal degradation of biogenic organic matter, i.e., graphitic carbon (e.g., Dodd et al, 2019), are also absent. A lack of functional groups is consistent with suggested abiotic CCM in serpentinites from the Ligurian Tethyan ophiolites (Sforna et al, 2018). It is also expected that any externally derived C-O-H fluids that could carry hydrocarbons would result in homogeneously distributed organics within pore spaces rather than the specific association to Fe oxides observed here.…”
Section: Origin Of the Condensed Carbonaceous Mattersupporting
confidence: 88%
See 1 more Smart Citation
“…Vibrational modes characteristic for thermal degradation of biogenic organic matter, i.e., graphitic carbon (e.g., Dodd et al, 2019), are also absent. A lack of functional groups is consistent with suggested abiotic CCM in serpentinites from the Ligurian Tethyan ophiolites (Sforna et al, 2018). It is also expected that any externally derived C-O-H fluids that could carry hydrocarbons would result in homogeneously distributed organics within pore spaces rather than the specific association to Fe oxides observed here.…”
Section: Origin Of the Condensed Carbonaceous Mattersupporting
confidence: 88%
“…For example, Ménez et al (2018) reported the occurrence of serpentinite-hosted abiotic amino acids, which they interpreted to have formed via Friedel-Crafts reactions catalyzed by Fe-rich saponite clay. This observation, among others (e.g., Sforna et al, 2018), suggests that complex organics can form abiotically via mineral-based catalysis during serpentinization. Beyond clay minerals, primary chromite grains (Foustoukos and Seyfried, 2004) as well as Fe oxides (e.g., Fe 3 O 4 ; Fu et al, 2007), Ni-Fe alloys (Horita and Berndt, 1999), and Fe-Ni sulfides (Camprubi et al, 2017) produced during serpentinization are thought to exert a first-order control on the abiogenic synthesis of organic matter.…”
Section: Introductionmentioning
confidence: 63%
“…Abiotic organic synthesis in the oceanic lithosphere, including Fischer-Tropschtype reactions (150-350°C), re-speciation and high temperature reactions (>400-500°C) of C-O-H fluids during magma cooling, and carbonate decomposition to CH 4 (<800°C), may also produce organic matter with a similar range of δ 13 C values, but they dominantly form methane and short chain hydrocarbons (Andreani and Ménez, 2019) and their required temperatures are inconsistent with the low temperature (20-89°C) zeolite facies rocks studied here. Although some evidence suggests abiotic carbonaceous matter can be formed during low temperature alteration of ocean crust (<150°C), it would have a distinct chemical composition containing aromatic carbon and short aliphatic chains (Sforna et al, 2018). Raman analysis shows that the intensity ratio of the D and G bands for DCM is 0.76 ( Fig.…”
Section: Lettermentioning
confidence: 99%
“…For example, high concentrations of dissolved organic material have been detected in close association with serpentine-hosted hydrogarnets recovered from the Mid-Atlantic Ridge. This material may have been produced by past microbiological activity (12) or by purely abiotic mechanisms (13). Acetate in endmember fluids at the Lost City Hydrothermal Field is likely produced by biological activity (14), but other hydrocarbons in the rock-hosted fluids do not have a clear biotic or abiotic source (15), though formate and C 2 ϩ alkanes appear to be produced abiotically (9,14).…”
mentioning
confidence: 99%